AN ANALYSIS OF DIRECT CAUSES OF MATERNAL MORTALITY - Rahim, Rehana; Shafqat, Tanveer; Faiz, Nasreen Ruby (Journal of Postgraduate Medical Institute, 2011)
Objective: This study was conducted to analyze the direct causes of maternal mortality during a period of seven years in a tertiary care hospital of NWFP. Material and Methods: This retrospective, analytic study was conducted from 1998-2004, and included all the pregnant patients including miscarriage and ectopic pregnancies, presenting during this period to Gynae B Unit, Lady Reading Hospital Peshawar. The records of maternal deaths were reviewed from 1998- 2004 retrospectively and causes of direct deaths were analyzed. Deaths in non-pregnant patients and indirect deaths in pregnant patients were excluded. Results: Total number of live births during the time period was 23720 and total number of maternal deaths was 311. The maternal mortality ratio (MMR) was calculated as 1311/100,000 live births. Out of 311 maternal deaths, 268 (86.2%) had direct causes and 43 (13.8%) had indirect causes of maternal mortality. Haemorrhage was responsible for 42.16% (113/268) of maternal deaths, followed by hypertensive disorders in 24.63% (66/268), ruptured uterus in 10.45% (28/268), septicemia in 9.7% (26/268), thrombo-embolism in 7.8% (21/268) and unsafe abortion in 3.4% (9/268) cases. Conclusion: The study shows a very high MMR as compared to national figures. The leading cause of direct maternal death was hemorrhage, followed by pregnancy induced hypertension, ruptured uterus and septicemia. These conditions can be prevented by good antenatal, intranatal and postnatal care.